Analysis of a blockstream in the northern Lesotho Drakensberg, southern Africa. (20th February 2022) - Bregman, Alexandra; Knight, Jasper
Abstract: Blockstreams are found in many mountain ranges worldwide and can be considered as an expression of the interplay between upslope sediment supply and transport-limited capacity of slope sediment systems. In mountain settings, blockstreams have been most commonly described as periglacial landforms, whose development and internal morphology reflect active layer processes, and where the landforms are not active under present climatic conditions. In the Maloti–Drakensberg mountain range of eastern Lesotho, southern Africa, several blockstreams have been identified but their age, evolution and relationships to climatic conditions are largely not known. This study maps and analyses the properties of one large blockstream in the Maloti–Drakensberg using field measurement techniques including Schmidt hammer relative exposure age dating of blockstream boulders. Results show that the blockstream is a relict feature but debris may have been derived from several sources including from periglacial slope activity. The presence of arcuate flow lobes within the main body of the studied blockstream attests to phases of slope-driven boulder movement possibly controlled by active-layer processes and cryoturbation, or by slip at the base of the sediment body driven by seasonal water availability. Relative age data from Schmidt hammer analysis suggest that different parts of the blockstream may have different ages and/or sources. By comparison with blockstreams elsewhere in the Maloti–Drakensberg, it is likely that it is of late Quaternary and probably of local last glacial maximum age, but younger Holocene phases of activity cannot be excluded.